Modern art in Egypt: Making the Old, New - Mostafa El-Razzaz (Alexandria; Bibliotheca Alexandria : Cultnat, the Center for Documentation of Cultural and Natural Heritage, 2019)
In the course of 5000 years, all cultures have to contend with the arrival of people, whether by conquest or migration, and being converted by them. Instead, the pattern in Egypt has been to absorb these foreign influences. Its artists have appreciated arriving talent, and have even become infatuated with it, taking its lessons. Eventually, they made it their own. Today's Egyptian artists are doing the same. Foreword: el Feki, Mostafa ; Author El-Razzaz, Mostafa; Graphic design Moheb, Marco; Photo editing Afify, Walaa; Proof reading El-Shaboury, Eman; Cover design Hawas, Tarek.
English
Keywords: Historic overview; Modernism in art; N5300-7418 Visual Arts- History; Egypt